Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
A = 1 + 2 + 22 + 23 + 24 + ..... + 22021
2A = 2 + 22 + 23 + 24 + 25 + ..... + 22022
2A - A = ( 2 + 22 + 23 + 24 + 25 + ..... + 22022 ) - ( 1 + 2 + 22 + 23 + 24 + ..... + 22021 )
A = 22022 - 1
Câu 2:
\(a,\Rightarrow x=-23+15=-8\\ b,\Rightarrow5\left(x+4\right)=85\\ \Rightarrow x+4=17\Rightarrow x=13\\ c,\Rightarrow5^{x+2}=24+1=25=5^2\\ \Rightarrow x+2=2\Rightarrow x=0\\ d,\Rightarrow x+4+x+5⋮9\\ \Rightarrow2x+9⋮9\\ \Rightarrow2x⋮9\Rightarrow x\in\left\{0;9\right\}\left(0< x< 10\right)\)
1)5x+1 + 6.5x+1 = 875
5x+1 ( 1+6 ) = 875
5x+1 . 7 = 875
5x+1 = 875 : 7
5x+1 = 125
5x+1 = 53
x+1 = 3
x = 3 - 1
x = 2
2)3x+1 + 3x+3 = 810
3x . 3 + 32 . 3x+1 = 810
3x . 3 + 9 . 3x . 3 = 810
3x .3 ( 1 + 9 ) = 810
3x+1 . 10 = 810
3x+1 = 810 : 10
3x+1 = 81
3x+1 = 34
x+1 = 4
x = 4-1
x = 3
Mình làm ngắn gọn nhé.
\(A=1+2+2^2+...+2^{50}\)
\(\Rightarrow2A=2+2^2+...+2^{51}\)
\(\Rightarrow2A-A=2+2^2+...+2^{51}-1-2-2^2-...-2^{50}\)
\(\Rightarrow A=2^{51}-1\)
\(B=1+3+...+3^{66}\)
\(3B=3+3^2+...+3^{67}\)
\(2B=3+3^2+...+3^{67}-1-3-...-3^{66}\)
\(2B=3^{67}-1\)
\(B=\frac{3^{67}-1}{2}\)
\(A=1+2^2+2^3+...+2^{2022}\)
\(\Rightarrow2A=2+2^3+2^4+...+2^{2023}\)
\(\Rightarrow A=2A-A=2+2^3+...+2^{2023}-1-2^2-...-2^{2022}=2-1+2^{2023}-2^2=-3+2^{2023}\)
A = 1 + 22 + 23 + ..... + 22021 + 22022
2A = 2(1 + 22 + 23 + ..... + 22021 + 22022)
2A = 2 + 23 + 24 + ..... + 22022 + 22023
2A - A = (2+23 + 24 + ..... + 22022 + 22023) - (1 + 22 + 23 + .... + 22021 + 22022 )
Thấy sai sai sao í -))
a) ta có: A = 3^0 + 3^1 + 3^2 + ...+ 3^100
=> 3A = 3^1 + 3^2 + 3^3 + ...+ 3^101
=> 3A-A = 3^101 - 3^0
2A = 3^101 - 1
\(A=\frac{3^{101}-1}{2}\)
b) D = 1 - 5 + 5^2 - 5^3 + ...+ 5^98 - 5^99
=> 5D = 5 - 5^2 + 5^3 - 5^4+...+ 5^99 - 5^100
=> 5D+D = -5^100 + 1
6D = -5^100 + 1
\(D=\frac{-5^{100}+1}{6}\)
2A=22+23+....+22022)
2A-A=(22+23+...+22022)-(2+22+....+22021)
A=22022-2
Đây nhé!